Implementasi Penyelesaian Sengketa Ekonomi Syariah menurut Perma No. 1 Tahun 2016 pada Lingkungan Peradilan Agama - Dudung Hidayat (CV. Syntax Corporation Indonesia, 2022)
Supreme Court Regulation No. 1 of 2016 on Mediation Procedures in court. Civil cases registered in the Court before entering into trial, must first be mediated with the help of a mediator. If mediation is unsuccessful, the case will proceed to trial and if mediation is not successful, the case will be null and void. The number of cases entered after the enactment of Supreme Court Regulation No. 1 of 2016 in the Religious Court is 6 cases. Of the 6 cases, 5 cases were unsuccessfully mediated and 1 case was revoked. This study aims to determine the implementation of mediation and the effectiveness of the application of Supreme Court Regulation Number 1 of 2016, in the settlement of sharia economic disputes at the Wonogiri Religious Court. This research is a field research. Data collection was conducted by interviewing mediator judges of Wonogiri Religious Court and documentation. By using qualitative descriptive analysis techniques. The result of this research is that mediation at the Wonogiri Religious Court has not been effective, this is due to community factors or the parties. Due to one of the parties feeling on the right side, the absence of the parties, bound by a notary agreement and the losses arising from sharia economic disputes.